2006
DOI: 10.1007/s10811-006-9102-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of photosynthesis in intertidal Mazzaella laminarioides (Bory)Fredericq (Rhodophyta, Gigartinales)

Abstract: The red alga Mazzaella laminarioides is an economically important species with an extended latitudinal distribution along the Chilean coast. Its populations form mid-intertidal stands, several meters wide, and therefore are differentially exposed to environmental variables that result in temporal and spatial variability in productivity. We evaluated the effect of latitude and intertidal height on productivity by in situ measurement of photosynthetic performance. Daily and seasonal variations of O 2 -evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
(63 reference statements)
0
12
0
1
Order By: Relevance
“…However, our results and information available in a few previous studies on the life cycle of this species, support the hypothesis that the degree of tolerance to desiccation is related to the position of this species in the upper-middle intertidal zone. For example, it was demonstrated that individuals of M. laminarioides from different heights at the intertidal zone, exhibited differential physiological responses to desiccation (photosynthetic performance, Varela et al 2006). In a broader context, individuals from higher on the rocky shore are reportedly more tolerant to desiccation than those further down.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results and information available in a few previous studies on the life cycle of this species, support the hypothesis that the degree of tolerance to desiccation is related to the position of this species in the upper-middle intertidal zone. For example, it was demonstrated that individuals of M. laminarioides from different heights at the intertidal zone, exhibited differential physiological responses to desiccation (photosynthetic performance, Varela et al 2006). In a broader context, individuals from higher on the rocky shore are reportedly more tolerant to desiccation than those further down.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is partially supported by studies showing that (1) individuals of the same species growing at different intertidal heights have different physiological capacities to recover from desiccation and (2) those living higher on the intertidal display higher tolerance to desiccation (Davison and Pearson 1996;Abe et al 2001;Burritt et al 2002;Varela et al 2006). Thus, this work evaluated the effect of desiccation on the early development of algal species with discrete vertical distribution in the intertidal zone.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 94%
“…For example, seasonal patterns in in situ photophysiology in the UK were almost identical between the two species, with no significant difference in F v /F m , rETR max , α or E k observed. Furthermore, where interspecific differences were apparent in situ, these reflected local responses to differential abiotic stress given their respective positions on the shore (Varela et al, 2006), and were absent with removal for ex situ analyses of photochemistry. Known differences in the global distributions of the Corallina species studied here (Williamson et al, 2015) do not, therefore, appear to relate to differential capacity for photochemistry.…”
Section: Interspecific Differences In Photochemistrymentioning
confidence: 99%
“…Additionally, independent studies have shown that diverse physiological parameters are altered by desiccation including the lipid and protein levels (Abe et al, 2001), photosynthetic alterations (Fv/Fm) as well as cellular morphology and ontogenetic changes (e.g. Contreras-Porcia et al, 2011b;Varela et al, 2006). Moreover, in microalgae it has been shown that salt (i.e.…”
Section: Introductionmentioning
confidence: 99%